2022
DOI: 10.3390/antiox11112092
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Thiosulphate-Loaded Liposomes Control Hydrogen Sulphide Release and Retain Its Biological Properties in Hypoxia-like Environment

Abstract: Hypoxia, or insufficient oxygen availability is a common feature in the development of a myriad of cardiovascular-related conditions including ischemic disease. Hydrogen sulphide (H2S) donors, such as sodium thiosulphate (STS), are known for their cardioprotective properties. However, H2S due to its gaseous nature, is released and cleared rapidly, limiting its potential translation to clinical settings. For the first time, we developed and characterised liposome formulations encapsulating STS and explored thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In other scenarios of human disease, preclinical studies of nanoparticle delivery of drugs have reported that nanoparticles could not only increase the compounds half-life time but also decrease the amount of drug being eliminated by the reticuloendothelial system, thus, improving stability and increasing drug exposure [ 106 , 107 ]. Recently, in our laboratory, we have explored nanoparticle approaches to encapsulate H 2 S donors, protecting from rapid degradation and release of H 2 S whilst exploring different routes of administration aiming to reduce administration regimes [ 108 110 ]. Whilst observations must be confirmed in an in vivo setting, it was noted that liposomes employed to carry ADT-OH across murine skin observed a delayed flux across the skin compared to formulations without liposomes suggesting liposomes may be beneficial in giving a controlled release of drug [ 108 ].…”
Section: Perspectives: Overcoming Limitations In H 2 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In other scenarios of human disease, preclinical studies of nanoparticle delivery of drugs have reported that nanoparticles could not only increase the compounds half-life time but also decrease the amount of drug being eliminated by the reticuloendothelial system, thus, improving stability and increasing drug exposure [ 106 , 107 ]. Recently, in our laboratory, we have explored nanoparticle approaches to encapsulate H 2 S donors, protecting from rapid degradation and release of H 2 S whilst exploring different routes of administration aiming to reduce administration regimes [ 108 110 ]. Whilst observations must be confirmed in an in vivo setting, it was noted that liposomes employed to carry ADT-OH across murine skin observed a delayed flux across the skin compared to formulations without liposomes suggesting liposomes may be beneficial in giving a controlled release of drug [ 108 ].…”
Section: Perspectives: Overcoming Limitations In H 2 ...mentioning
confidence: 99%
“…Whilst observations must be confirmed in an in vivo setting, it was noted that liposomes employed to carry ADT-OH across murine skin observed a delayed flux across the skin compared to formulations without liposomes suggesting liposomes may be beneficial in giving a controlled release of drug [ 108 ]. Furthermore, cationic liposomes used in the controlled release of H 2 S from sodium thiosulphate were able to retain its biological properties in hypoxia-like environment [ 110 ]. Finally, PLGA nanoparticles carrying sodium thiosulphate observed a sustained cellular drug uptake whilst maintaining the pro-angiogenic potential of H 2 S [ 109 ].…”
Section: Perspectives: Overcoming Limitations In H 2 ...mentioning
confidence: 99%